Ergonomics Evaluation on Non Keyboard Input Devices - syed mohamed, muhammad syafiq; Ze Mei, Chiang; Hui Hui, Yee (CENTRE OF PROMOTING RESEARCH EXCELLENCE (CPRE), 2013)

(untitled)
A pilot study was conducted on the ergonomic aspects of computer mouse designs. The wrist posture position was studied for an extra small mouse, a standard mouse and a gaming mouse. Ten Malaysian undergraduate students consisting of 5 males and 5 females aged between 18 to 25 years old were selected for the pilot study. They performed right-handed mouse activities which involve positioning of the cursor, drawing, clicking, dragging and scrolling. Wrist deviations were found to be at 38 degrees for the extra small mouse, 20 degrees for the standard mouse and 25 degrees for the gaming mouse. No significant difference was found for the task times for all the three mice designs. Upon comparison of the three different mouse designs, the ergonomic mouse was found to provide comfort, reduce risk of injuries and maximize productivity of users.